﻿Studi Kasus Penatalaksanaan Terapi Okupasi BersumberdayaMasyarakat Dalam Aktivitas Memasak Pada Penderita StrokeDi Desa Setisari - ﻿Gidion, ﻿Hermito; ﻿Luthfi, ﻿Muhammad; ﻿Fajariani, ﻿Dini; ﻿Pratama, ﻿Aditya ﻿Denny (UI Scholars Hub, 2022)
Stroke is a health problem that affects a person's independence. Occupational therapists can carry out community-based occupational therapy (TOBM) in intervening in stroke patients. The aim of this intervention is to improve the patient's ability to cook from an occupational therapy perspective. In community service through TOBM, stroke patients in Siteari village were given an intervention for 1 month to assess an increase in independence in cooking. There are results that TOBM can increase patient independence in cooking.